2-Methoxyestradiol Damages DNA in Glioblastoma Cells by Regulating nNOS and Heat Shock Proteins - Paulina Emilia Bastian; Agnieszka Daca; Agata Płoska; Alicja Kuban-Jankowska; Leszek Kalinowski; Magdalena Gorska-Ponikowska (MDPI AG, 2022)
Gliomas are the most prevalent primary tumors of the central nervous system (CNS), accounting for over fifty percent of all primary intracranial neoplasms. Glioblastoma (GBM) is the most prevalent form of malignant glioma and is often incurable. The main distinguishing trait of GBM is the presence of hypoxic regions accompanied by enhanced angiogenesis. 2-Methoxyestradiol (2-ME) is a well-established antiangiogenic and antiproliferative drug. In current clinical studies, 2-ME, known as Panzem, was examined for breast, ovarian, prostate, and multiple myeloma. The SW1088 grade III glioma cell line was treated with pharmacological and physiological doses of 2-ME. The induction of apoptosis and necrosis, oxidative stress, cell cycle arrest, and mitochondrial membrane potential were established by flow cytometry. Confocal microscopy was used to detect DNA damage. The Western blot technique determined the level of nitric oxide synthase and heat shock proteins. Here, for the first time, 2-ME is shown to induce nitro-oxidative stress with the concomitant modulation of heat shock proteins (HSPs) in the SW1088 grade III glioma cell line. Crucial therapeutic strategies for GMB should address both cell proliferation and angiogenesis, and due to the above, 2-ME seems to be a perfect candidate for GBM therapy.